Analysis of the Effect of Biomass Sawdust Co-firing on the Operational Parameters and Maintenance Policies of Pulverized Coal Type Boilers at Indramayu Power Plant - El Nur, Abdillah Irsyad; Jenny Rizkiana (ITB Graduate School Conference, 2025)
This study evaluates the implementation of co-firing 5% sawdust with 95% coal at the Indramayu Power Plant, focusing on fuel characteristics, operational performance of the pulverizer and boiler, steam and electricity generation, and the post-operation condition of boiler tube thickness. Sawdust has a lower calorific value (3717 kCal/kg) compared to coal (3807 kCal/kg) and a high moisture content (51.42%), both of which influence combustion efficiency. However, its very low sulfur (0.01%) and nitrogen (0.42%) content suggests potential for emission reduction. During 24 hours of operation, the pulverizer system showed a maximum motor current of 39.11 Amperes and an outlet temperature range of 56–64 °C, indicating safe and stable performance. The boiler system remained optimal with a superheater outlet temperature of 623 °C and a primary steam pressure of 16.83 MPa. A reduction of 0.29 mm in boiler tube thickness was observed in the superheater area, likely due to prolonged exposure to high temperatures, but still within acceptable safety margins. The results confirm that co-firing 5% sawdust is technically feasible without compromising plant reliability. Nonetheless, precise combustion control and continuous monitoring of emissions and material degradation are necessary to ensure longterm operational safety and environmental compliance.